Odpowiedź :
Odpowiedź:
d) [tex]\frac{7}{6}+(-\frac{5}{4}-\frac{4}{3})=\frac{7}{6}+(-\frac{15}{12}-\frac{16}{12})=\frac{14}{12}+(-\frac{31}{12})=\frac{14}{12}-\frac{31}{12}=-\frac{17}{12}\\[/tex]
e) [tex]-(-2\frac{2}{3})+\frac{7}{15}=\frac{8}{3}+\frac{7}{15}=\frac{40}{15}+\frac{7}{15}=\frac{47}{15}=3\frac{2}{15}[/tex]
f) [tex]-1\frac{9}{16}+\frac{11}{12}=-\frac{25}{16}+\frac{11}{12}=\frac{75}{48}+\frac{44}{48}=\frac{119}{48}=2\frac{23}{48}[/tex]
g) [tex]1\frac{5}{8}-(-2\frac{2}{3}+0,25) = \frac{13}{8}-(-\frac{8}{3}+\frac{1}{4})=\frac{39}{24}-(-\frac{64}{24}+\frac{6}{24})=\frac{39}{24}+\frac{58}{24}=\frac{94}{24}=3\frac{22}{24}[/tex]
h) [tex]1\frac{2}{5}-3\frac{7}{8}-0,125=\frac{7}{5}-\frac{31}{8}-\frac{1}{8}=\frac{56}{40}-\frac{155}{40}-\frac{5}{40}=-\frac{94}{40}=-2\frac{7}{20}[/tex]
i) [tex]\frac{1}{2}-\frac{1}{3}-(\frac{1}{4}-\frac{1}{5})=\frac{3}{6}-\frac{2}{6}-(\frac{5}{20}-\frac{4}{20})=\frac{1}{6}-\frac{1}{20}=\frac{10}{60}-\frac{3}{60}=\frac{7}{60}[/tex]